Phenolic amides with anti-Parkinson's disease (PD) effects from Nicandra physaloides. (April 2017) - Wang, Li-Qing; Wang, Ying; Gao, Su-Yu; Zhu, Li-Han; Wang, Fei; Li, Hua; Chen, Li-Xia
Highlights: Two new phenolic amides and twelve known derivatives were isolated from N. physaloides. The protective effects on damaged SH-SY5Y cells of the compounds were evaluated. The plausible biosynthetic pathway of phenolic amide compounds was discussed. Abstract: Nicandra physaloides is a traditional folk medicine in China, and its seeds are used to make jelly. Phytochemical investigation of the active ethyl acetate (EtOAc) extract of its fruits led to the isolation and identification of two new phenolic amides, (7 R, 8S)-7-(4-hydroxy-3, 5-dimethoxyphenyl)-8-hydroxymethyl-1′-[N-7″-(4″-hydrxyphenyl)ethyl]carbamoylethenyl-3′-methoxybenzodihydrofuran (1 ) and cis -N-phydroxycinnamoyl-7′-methoxyethyltyramine (2 ), together with twelve known compounds (3 –14 ). Their structures were determined on the basis of spectroscopic analyses. All these compounds are reported from the genus Nicandra for the first time. Compounds1 –14 were investigated for their protective effects on 1-methyl-4-phenylpyridiniumion (MPP + )-induced damage in human dopaminergic neuroblastoma cells (SH-SY5Y), and compounds4, 6 and7 showed significant protective activities at a certain concentration. Further, the cell protection mechanism of compound4 was proved to be through inhibiting MPP + -induced apoptosis and inducing cytoprotective autophagy in Parkinson's disease (PD). Herein, a plausible biosynthetic pathway of compounds1 –14 was also discussed. This study suggested that phenolic amides were potential candidate drugs for treating PD and the fruits of N. physaloides could be used as a functional food ingredient to improve the symptoms of memory loss, and possibly to prevent or treat PD.